The Effect of Animated Movies and Nursery Rhymes on Early Childhood English Speaking Skills - Nurhayati; Susanti, Debbie (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study investigates the influence of animated films and nursery rhymes on English speaking abilities of early childhood students in West Bekasi District. Using a quantitative associative approach, the research involved 64 children aged 4-6 years from 16 kindergartens. Data was collected through speaking tests, questionnaires, and documentation. The study employed descriptive analysis, Spearman correlation, and ordinal regression analysis. Results show that both animated films (rs = 0.612, p < 0.001) and nursery rhymes (rs = 0.639, p < 0.001) have a strong positive correlation with children's English speaking abilities. Ordinal regression analysis reveals significant positive effects of animated films (β = 0.931, p < 0.001) and nursery rhymes (β = 1.058, p < 0.001) on speaking abilities. The combined use of both media demonstrated a synergistic effect, supporting multisensory approaches in language learning. The model explains 57.3% of the variation in children's English speaking abilities, indicating good predictive power. These findings provide empirical evidence for the effectiveness of audiovisual media in early childhood English language learning, supporting multimedia learning theory and dual coding theory. The study concludes that integrating animated films and nursery rhymes into early childhood English curricula can significantly enhance speaking abilities, offering valuable insights for educators and curriculum developers in designing effective language learning strategies for young children